Progressive choreodystonia in X-linked hyper-IgM immunodeficiency: a rare but recurrent presentation - Škorvánek, Matej; Jech, Robert; Winkelmann, Juliane; Zech, Michael (Annals of clinical and translational neurology, 2022)
An association between movement disorders and immune-system dysfunction has been described in the context of rare genetic diseases such as ataxia telangiectasia as well as infectious encephalopathies. We encountered a male patient who presented immunodeficiency of unknown etiology since childhood. A medication-refractory, progressive choreodystonic movement disorder emerged at the age of 42 years and prompted an exome-wide molecular testing approach. This revealed a pathogenic hemizygous variant in CD40LG, the gene implicated in X-linked hyper-IgM syndrome. Only two prior reports have specifically suggested a causal relationship between CD40LG mutations and involuntary hyperkinetic movements. Our findings thus confirm the existence of a particular CD40LG-related condition, combining features of compromised immunity with neurodegenerative movement abnormalities. Establishing the diagnosis is crucial because of potential life-threatening immunological complications.
Keywords: Child; ligand CD40; Hyper-IgM Immunodeficiency Syndrome, Type 1; dítě; Adult; Male; Mutation; mutace; lidé; dospělí; mužské pohlaví; Humans; imunodeficience s hyper-IgM, typ 1; CD40 Ligand